Hydrogen-atom transfer (HAT) initiated by intramolecular ligand-metal electron transfer - Herrmann, Hendrik Hans; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2017)
Hydrogen-atom transfer (HAT) is of key importance for several catalytic and biological processes, and provides an elegant access to C−H activation. In synthetic chemistry, a photoactivated metal complex is often employed to abstract an oxygen- or nitrogen-bound hydrogen, and the as-generated oxygen- or nitrogen-centered radical is the hydrogen-atom acceptor for HAT. Here, we report the first examples for HAT processes initiated by one-electron oxidation of urea azines. A further novelty is that the HAT-initiating oxidation can be realized by intramolecular ligand-metal electron transfer in copper(II)-urea azine complexes. These complexes are first characterized in the solid state, in which they are stable. Electron-transfer-initiated HAT processes are observed upon dissolving the complexes in organic solvents, and the kinetics of these processes varies with the solvent polarity. The carbon-centered radicals formed by HAT can either be trapped with 2,2,6,6-tetramethylpiperidinyloxyl (TEMPO) or undergo radical recombination reactions with itself, yielding diamagnetic end-products.